2022
DOI: 10.36419/jki.v14i1.762
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Konsumsi Kurma Ajwa Terhadap Kontraksi Uterus Dilihat Dari Lama Persalinan

Abstract: ABSTRAKLatar Belakang : Kelainan pada lamanya persalinan salah satunya dikaitkan pada kelainan his dengan kekuatan yang lemah atau tidak adekuat untuk melakukan pembukaan serviks atau mendorong anak keluar. Hal ini sering dijumpai pada ibu bersalin dengan anemia yang berkaitan langsung dengan gizi pada saat kehamilan. Kurma merupakan salah satu makanan yang memiliki kandungan gizi yang baik yang sangat bermanfaat bagi ibu maupun janin. Peran kurma dalam persalinan memiliki efek yang signifikan sebagai dilatasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Twenty-eight publications addressed the labor duration in either the latent phase ( n = 3), active phase ( n = 11), the first stage ( n = 14), the second stage ( n = 16), or the third stage ( n = 12), as well as in total ( n = 5) [ 28 – 37 , 39 , 57 , 59 – 63 , 65 , 75 , 77 – 85 ]. Two publications had the same participants [ 62 , 63 ]; hence, we excluded one with a smaller sample size from the meta-analysis [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-eight publications addressed the labor duration in either the latent phase ( n = 3), active phase ( n = 11), the first stage ( n = 14), the second stage ( n = 16), or the third stage ( n = 12), as well as in total ( n = 5) [ 28 – 37 , 39 , 57 , 59 – 63 , 65 , 75 , 77 – 85 ]. Two publications had the same participants [ 62 , 63 ]; hence, we excluded one with a smaller sample size from the meta-analysis [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the meta-analysis did not include eight other studies because they reported only categorical data ( n = 6) [ 32 , 33 , 36 , 37 , 81 , 84 ] or did not report the SDs ( n = 2) [ 60 , 61 ]. Alao, meta-analysis was not performed on two non-RCTs that reported the effectiveness of dates consumption during late pregnancy in reducing total labor duration [ 39 , 77 ], considering the insufficient ESs. Hence, 17 trials were suitable for meta-analysis of labor duration.…”
Section: Resultsmentioning
confidence: 99%